Multiple crises and global health: New and necessary frontiers of health politics - Schrecker, Ted (Université d'Ottawa | University of Ottawa, 2012)
The world economy is entering an era of multiple crises, involving finance, food security and global environmental change. This article assesses the implications for global public health, describes the contours of post-2007 crises in food security and finance, and then briefly indicates the probable health impacts. There follows a discussion of the crisis of climate change, one that will unfold over a longer time frame but with manifestations that may already be upon us. The article then discusses the political economy of responses to these crises, noting the formidable obstacles that exist to equitable resolution. The article concludes by noting the threat that such crises present to recent progress in global health, arguing that global health researchers and practitioners must become more familiar with the relevant social processes, and that proposed solutions that neglect the continuing importance of the nation-state are misdirected.
Keywords: crises; financial crises; food security; food prices; globalisation; land grabs; climate change; global environmental change